Workshop report: Developing a methodology to communicate climate services for farmers at scale - May S; Hansen, James; Tall, Arame (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This report summarizes the proceedings of the workshop; “Developing a Methodology to Communicate Climate Services At Scale Through Intermediaries for Farmer Communities in Africa and South Asia,” held in Nairobi, Kenya on June 12-14, 2013. The workshop brought together experts from different countries and institutions to work together to develop tools and guidance materials to train various intermediary groups in climate service communication, including public extension services, professional communicators, media, rural radios, NGOs, CBOs, farmers’ organizations, women self help groups and other boundary organizations. Participants developed an outline of potential training modules, and committed to contributing and further developing materials for a training resource guidebook.